1991
DOI: 10.1017/s0016672300029062
|View full text |Cite
|
Sign up to set email alerts
|

Mixed model analysis of a selection experiment for food intake in mice

Abstract: Data from 23 generations of mice selected for increased and reduced appetite were analysed by Restricted Maximum Likelihood fitting an animal model with litters as additional random effects. Traits considered were food intake between 4 and 6 weeks of age adjusted for 4-week body weight (AFI), the selection criterion, and body weight at 6 weeks (6WW). Selection was carried out within families. A high and a low selection line and a control were maintained in each of three replicates. Analyses were performed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 20 publications
1
43
0
3
Order By: Relevance
“…In theory, REML techniques using an animal model and complete relationship matrix yield unbiased estimated of base population parameters (Johnson et al, 1995). However, Meyer & Hill (1991) found that REML analyses did not account for a decrease in genetic variance in the analyses of 23 generations of selection in mice. …”
Section: Resultsmentioning
confidence: 99%
“…In theory, REML techniques using an animal model and complete relationship matrix yield unbiased estimated of base population parameters (Johnson et al, 1995). However, Meyer & Hill (1991) found that REML analyses did not account for a decrease in genetic variance in the analyses of 23 generations of selection in mice. …”
Section: Resultsmentioning
confidence: 99%
“…Bryant and Meffert (1988) found that G changed in shape following population bottlenecks in the housefly Musca domestica, and we have shown that G can change drastically as a result of population bottlenecks in D. melanogaster (Phillips et al 2001). Many other studies have shown changes in the additive genetic variance during selection (Wilkinson et al 1990;Meyer and Hill 1991; Beniwal et al 1992a,b;Shaw et al 1995) or after inbreeding or population bottlenecks (Frankham 1980;Bryant et al 1986;Briscoe et al 1992; Whitlock and Fowler 1999 and references therein). These changes in G after inbreeding may be transient, though, because the evolutionary forces such as selection and mutation that act to determine G may return it to its previous shape (although see Camara et al 2000).…”
mentioning
confidence: 98%
“…In this case, the animal model may not yield a strict estimate of G in the base parental population, but one that is 'biased' towards subsequent generations for which data are included. Further research is required to better understand exactly how animal models perform in such situations [25]. To ensure the differences found were attributable to selection per se and not genetic drift, we also ran MCMC models on a line-by-line basis, which yielded a total of 24 G matrices for comparison (i.e.…”
Section: (C) Animal Models For Quantitative Genetic Analysesmentioning
confidence: 99%